Determination of ploidy of a dimorphic zygomycete Benjaminiella poitrasii and the occurrence of meiotic division during zygospore germination - Ghormade, V.; Shastry, P.; Chiplunkar, J.; Deshpande, M.V. (International Journal of Agricultural Technology, 2005)
Benjaminiella poitrasii is a zygomycetous, dimorphic fungus which exists in yeast or hyphal forms during the vegetative phase and produces asexual sporangiospores and zygopores during the reproductive stage. The zygospores germinate either by germ-sporangiophore formation or hyphal formation. However, the budding type germination of zygospores of B. poitrasii was observed in response to high glucose, 37°C and pH 4.0; conditions favouring the yeast-form. The yeast cells from the budding zygospore were analysed to ascertain time and occurrence of meiotic division and to understand the change in the ploidy levels in its life-cycle. The ploidy and nuclear behaviour of this fungus were studied at different stages in the life cycle using the vegetative yeast cells, the asexual sporangiospores, and the yeast cells from the budding zygospore. The uninucleate sporangiospores and the multinucleate yeast cells showed similar DNA contents/nucleus as estimated by spectrophotometric DNA content estimation, survival in the presence of ultraviolet radiation and flow cytometry. The sporangiospores and yeast cells were in the haploid state. DAPI staining of the zygospore showed that few nuclei fused in the zygospore and underwent the meiotic division. The haploid nature of the yeast cells from the budding zygospore indicated that meiosis had occurred before the initiation of germination. The understanding of spore germination in B. poitrasii and its use as a model to screen antifungal agents is also discussed.